Electrode slurry and preparation method thereof, electrode plate, battery and electric device
By using self-assembled peptide nanotubes to coat active materials and conductive agents in lithium-ion battery electrode slurry, a three-dimensional network structure is formed, which solves the problems of high cost and complex process improvement in the current technology, and improves the battery rate performance and cycling performance.
Patent Information
- Application Number
- CN202411749475.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
The existing lithium-ion battery rate performance improvement methods have problems such as high cost, complex preparation process, and difficult control of pore uniformity and stability.
By adding self-assembled peptide nanotubes to the electrode slurry, the active material and conductive agent are coated to form a three-dimensional network structure, the electron conduction path is optimized, and the electron conduction path is interlocked with the binder, limiting the floating of the conductive agent and binder, and improving the uniformity of the electrode sheet.
It effectively improves the rate performance and circulation performance of lithium-ion batteries, while reducing costs and simplifying production processes.
Smart Images

Figure CN119560566A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to an electrode slurry and a preparation method thereof, an electrode sheet, a battery and an electrical device. Background Art
[0002] As the global energy crisis and environmental pollution become increasingly serious, the application of renewable energy has received unprecedented attention. As one of the key technologies for the use of renewable energy, batteries, especially lithium-ion batteries, play a vital role in new energy vehicles, energy storage systems, portable electronic devices and other fields. Lithium-ion batteries have become one of the most widely used types of batteries due to their high energy density, long cycle life and good safety.
[0003] However, for lithium-ion batteries, their rate performance, that is, the ability to complete charge and discharge in a short period of time, is an important factor in determining whether they can meet the needs of fast charging and high-power discharge. With the development of the electric vehicle market, consumers are increasingly concerned about the vehicle's endurance, prompting the demand for significantly improving charging speeds. Therefore, improving the rate performance of batteries has become one of the hot issues in the field of battery research.
[0004] At present, the industry mainly adopts the following technical means to improve the rate performance of lithium-ion batteries:
[0005] Material modification: Improve the conductivity and ion diffusion capacity of the material by chemically modifying or adjusting the structure of the positive or negative electrode material. For example, by doping with metal elements or carbon coating, the electronic conductivity of the material is increased and the transmission resistance of lithium ions in the material is reduced.
[0006] New process development: Use new coating technology or other manufacturing processes to improve the consistency and uniformity of battery components, thereby improving the overall performance of the battery. For example, multi-layer coating technology can effectively control the interface effect between layers of materials and improve the overall performance of the battery.
[0007] Pole sheet pore making: Micropores are formed on the electrode material through physical or chemical methods to increase the effective surface area of the electrode material and promote the rapid migration of lithium ions in the electrolyte, thereby improving the battery's rate performance.
[0008] CN113113565A discloses a negative electrode plate and a battery. Through double-layer coating technology, two layers of negative electrode graphite materials with different compaction densities and specific surface areas are arranged on the current collector, which increases the infiltration of the electrolyte, improves the lithium insertion capacity, and achieves a good balance between the battery energy density and rate performance.
[0009] CN216719994U discloses a pole piece preparation mold, a battery pole piece and a battery. A pore-forming device is arranged in the mold body, and the pore-forming device is used to insert into the mold body to form holes in the pole piece intermediate placed in the mold body to obtain a battery pole piece with a porous structure, thereby improving the electrolyte infiltration and rate performance of the battery, thereby increasing the thickness of the pole piece to prepare a porous ultra-thick pole piece, thereby achieving the purpose of reducing or eliminating the current collector and improving the weight energy density of the battery cell.
[0010] Although the existing methods can improve the rate performance to a certain extent, there are still some problems. For example, the modification of materials may encounter problems such as high cost and complicated preparation process in practical applications; the development of new processes and the hole making of the pole piece require corresponding equipment support and the process complexity is relatively high, especially in actual production, it is difficult to control the uniformity and stability of the pores made.
[0011] Therefore, how to further improve the rate performance of lithium-ion batteries without sacrificing other performance indicators while reducing costs and simplifying the production process remains one of the urgent problems to be solved in this field. Summary of the invention
[0012] In view of the problems existing in the prior art, the object of the present invention is to provide an electrode slurry and a preparation method thereof, an electrode sheet, a battery and an electrical device. The electrode slurry is prepared by adding a self-assembling peptide nanotube raw material to the slurry in the slurry mixing process, and the peptide nanotubes are generated by self-assembly to form a coating on the surface of the active material and the conductive agent, and further interlock with the binder to form a network structure, thereby optimizing the electron conduction path, and the obtained electrode slurry is conducive to limiting the floating of the binder and the conductive agent on the electrode sheet in the coating process, improving the distribution uniformity of the binder and the conductive agent on the electrode sheet, thereby improving the rate performance and cycle performance of the battery.
[0013] To achieve this object, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides an electrode slurry, which includes an active material, a conductive agent, a binder, a solvent and self-assembling peptide nanotubes; the self-assembling peptide nanotubes cover the active material and the conductive agent.
[0015] The present invention utilizes self-assembling peptide nanotubes in the electrode slurry to coat the active material and the conductive agent, thereby forming a three-dimensional network in the electrode slurry and in the active layer formed using the electrode slurry. On the one hand, the electron conduction path in the active layer formed by the electrode slurry can be optimized. On the other hand, the network structure of the peptide nanotubes can further interlock and cooperate with the binder, thereby improving the distribution uniformity of the conductive agent and the binder, enhancing the binding of the active material and the conductive agent and the uniformity of the formed active layer; at the same time, under the influence of the peptide nanotubes distributed in the slurry, during the coating process of the electrode slurry, it is beneficial to limit the floating of the binder and the conductive agent, thereby further improving the uniformity of the electrode sheet in the thickness direction. Therefore, the present invention can achieve effective improvement of the rate performance and cycle performance of the electrode sheet and the resulting battery from the slurry level and the manufacturing side of the electrode sheet.
[0016] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] It should be emphasized that the present invention achieves optimization, improvement and enhancement effects through the electrode slurry layer (the manufacturing side of the electrode sheet), so the working principle is not limited to the type of electrode sheet. At present, the positive and negative electrode sheets of lithium-ion batteries, the positive and negative electrode sheets of sodium-ion batteries, the positive and negative electrode sheets of potassium-ion batteries, and the positive and negative electrode sheets of magnesium-ion batteries are all suitable for the present invention.
[0018] As a preferred technical solution of the present invention, when the electrode slurry is a positive electrode slurry, the positive electrode slurry includes a positive electrode solvent, and a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and a first self-assembling peptide nanotube in a mass ratio of x:y:z:m; and x+y+z+m=100%, 85%≤x<100%, for example, x can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, etc.; 0<y<10%, for example, y can be 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.5%, etc.; 0<z<10%, for example, z can be For example, y+z may be 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.5%; 0<m<5%, for example, m may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 4.9%; 0.5%≤y+z≤10%, for example, y+z may be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0019] As a preferred technical solution of the present invention, the positive electrode active material includes at least one of a lithium ion battery positive electrode active material, a sodium ion battery positive electrode active material, a potassium ion battery positive electrode active material or a magnesium ion battery positive electrode active material.
[0020] Preferably, the positive electrode active material of the lithium-ion battery includes at least one of lithium cobalt oxide, ternary materials (such as nickel cobalt manganese NCM and / or nickel cobalt aluminum NCA), lithium-rich manganese-based materials, lithium iron phosphate or lithium iron manganese phosphate.
[0021] Preferably, the sodium ion battery positive electrode active material, potassium ion battery positive electrode active material or magnesium ion battery positive electrode active material is respectively selected from at least one of a layered oxide, a polyanion compound (such as sodium ion battery positive electrode active material sodium iron phosphate pyrophosphate) or a Prussian blue analogue.
[0022] Preferably, the positive electrode conductive agent includes at least one of conductive carbon black (such as acetylene black and / or Ketjen black), carbon nanotubes or graphene.
[0023] Preferably, the positive electrode binder includes polyvinylidene fluoride and / or polytetrafluoroethylene.
[0024] Preferably, the cathode solvent comprises N-methylpyrrolidone.
[0025] Preferably, the solid content of the positive electrode slurry is 45% to 85%, for example, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 63%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82% or 85%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0026] As a preferred technical solution of the present invention, when the electrode slurry is a negative electrode slurry, the negative electrode slurry includes a negative electrode solvent, and a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a second self-assembling peptide nanotube in a mass ratio of a:b:c:n; and a+b+c+n=100%, 85%≤a<100%, for example, a can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, etc.; 0<b<10%, for example, b can be 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.5%, etc.; 0<c<10%, for example, c can be For example, b+c may be 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 9.5%; 0<n<5%, for example, n may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 4.9%; 0.5%≤b+c≤10%, for example, b+c may be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other values not listed within the above numerical range are equally applicable.
[0027] As a preferred technical solution of the present invention, the negative electrode active main material includes at least one of graphite, hard carbon, silicon-based materials, lithium titanate or metal oxide negative electrode materials.
[0028] Preferably, the negative electrode conductive agent includes at least one of conductive carbon black (such as acetylene black and / or Ketjen black), carbon nanotubes, carbon fibers or graphene.
[0029] Preferably, the negative electrode binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose or polyacrylic acid.
[0030] Preferably, the negative electrode solvent includes pure water and / or N-methylpyrrolidone.
[0031] Preferably, the negative electrode slurry further includes a plasticizer.
[0032] Preferably, the plasticizer includes at least one of ethylene carbonate, propylene carbonate, 1,3-butanediol or N-methylpyrrolidone.
[0033] Preferably, the solid content of the negative electrode slurry is 40% to 65%, for example, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64% or 65%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0034] In a second aspect, the present invention provides a method for preparing the electrode slurry described in the first aspect, the preparation method comprising mixing and dispersing an active material, a conductive agent, a binder, a solvent and a self-assembling peptide nanotube raw material, and maintaining stirring and / or standing to allow the self-assembling peptide nanotube raw material to self-assemble, forming the self-assembling peptide nanotubes coating the active material and the conductive agent to obtain an electrode slurry.
[0035] As a preferred technical solution of the present invention, the raw material of the self-assembling peptide nanotubes includes phenylalanine dipeptide.
[0036] In the present invention, during the slurrying process of phenylalanine dipeptide with active materials, conductive agents, binders and solvents, phenylalanine dipeptide will self-assemble, and its self-assembly process will not cause any mass loss. By maintaining stirring and / or standing, until the phenylalanine dipeptide is completely self-assembled to fully exert its effect, it is ensured that the formed peptide nanotubes have a sufficient and appropriate amount to fully cover the active materials and conductive agents, and are interlocked with the binder, forming and maintaining a three-dimensional network in the electrode slurry and the formed active layer.
[0037] Preferably, the stirring time is 1 to 4 h, for example 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0038] In a third aspect, the present invention provides an electrode sheet obtained by sequentially coating, drying, rolling and die-cutting the electrode slurry described in the first aspect.
[0039] It should be noted that the present invention does not particularly limit the specific methods and parameters of coating, drying, rolling and die-cutting of the electrode slurry, and should be reasonably selected and adjusted according to actual conditions and needs. For example, when the positive electrode slurry of a lithium-ion battery is coated, the coated current collector includes aluminum foil; when the negative electrode slurry of a lithium-ion battery is coated, the coated current collector includes copper foil.
[0040] In a fourth aspect, the present invention provides a battery comprising the electrode sheet described in the third aspect.
[0041] In a fifth aspect, the present invention provides an electrical device comprising the battery described in the fourth aspect.
[0042] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0043] The present invention utilizes self-assembling peptide nanotubes in the electrode slurry to coat the active material and the conductive agent, thereby forming a three-dimensional network in the electrode slurry and in the active layer formed using the electrode slurry. On the one hand, the electron conduction path in the active layer formed using the electrode slurry can be optimized. On the other hand, the network structure of the peptide nanotubes can further interlock and cooperate with the binder, thereby improving the distribution uniformity of the conductive agent and the binder, enhancing the binding of the active material and the conductive agent and the uniformity of the formed active layer; at the same time, under the influence of the peptide nanotubes distributed in the slurry, during the coating process of the electrode slurry, it is beneficial to limit the floating of the binder and the conductive agent, thereby further improving the uniformity of the electrode sheet in the thickness direction. Therefore, the present invention can achieve effective improvement of the rate performance and cycle performance of the electrode sheet and the resulting battery from the slurry level and the manufacturing side of the electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a pulse performance test diagram of lithium-ion batteries B, C and D obtained in Application Example 2;
[0045] Figure 2 It is a cycle performance test diagram of lithium-ion batteries B, C and D obtained in Application Example 2;
[0046] Figure 3 1C discharge curve diagram of sodium battery X and sodium battery Z of sodium ion battery obtained in Application Example 2. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0048] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0049] Example 1
[0050] This embodiment provides a positive electrode slurry for a lithium-ion battery, including a positive electrode active material, lithium nickel cobalt manganese oxide, a positive electrode conductive agent, conductive carbon black, a positive electrode binder, polyvinylidene fluoride, a positive electrode solvent, N-methyl pyrrolidone, and self-assembling peptide nanotubes; the self-assembling peptide nanotubes coat the positive electrode active material and the positive electrode conductive agent;
[0051] The preparation method of the positive electrode slurry of a lithium ion battery comprises: adding phenylalanine dipeptide and N-methylpyrrolidone into a 30L slurry mixing kettle, fully dissolving and dispersing them to obtain a phenylalanine dipeptide solution; adding lithium nickel cobalt manganese oxide, conductive carbon black, polyvinylidene fluoride and phenylalanine dipeptide solution into a 30L slurry mixing kettle according to a mass ratio of pure substances (excluding solvent) of 95.4%:2%:2%:0.6%, stirring evenly, adding N-methylpyrrolidone to adjust the solid content to 72% of the total weight of the slurry, stirring at high speed to disperse evenly, and slowly stirring for 2.5 hours to obtain the positive electrode slurry of the lithium ion battery.
[0052] Example 2
[0053] This embodiment provides a negative electrode slurry for a lithium-ion battery, including negative electrode active material graphite, negative electrode conductive agent conductive carbon black, negative electrode binder carboxymethyl cellulose and styrene-butadiene rubber, negative electrode solvent pure water and self-assembling peptide nanotubes; the self-assembling peptide nanotubes coat the negative electrode active material and the negative electrode conductive agent;
[0054] The preparation method of the negative electrode slurry of the lithium ion battery comprises: adding carboxymethyl cellulose and pure water into a 30L slurry mixing kettle to disperse to obtain a glue solution. Adding the glue solution, graphite, conductive carbon black, and phenylalanine dipeptide into a 30L slurry mixing kettle according to the mass ratio of pure substances (excluding solvent) of 1%:94.4%:2%:0.6%, adding pure water, adjusting the solid content to 51% of the total weight of the slurry, stirring at high speed to disperse evenly, adding styrene-butadiene rubber with a mass ratio of 2%, and continuing to disperse to obtain the negative electrode slurry of the lithium ion battery.
[0055] Example 3
[0056] This embodiment provides a positive electrode slurry for a sodium ion battery, comprising a positive electrode active material, sodium iron phosphate pyrophosphate, a positive electrode conductive agent, conductive carbon black, a positive electrode binder, polyvinylidene fluoride, a positive electrode solvent, N-methylpyrrolidone, and self-assembling peptide nanotubes; the self-assembling peptide nanotubes coat the positive electrode active material and the positive electrode conductive agent;
[0057] The preparation method of the positive electrode slurry for a lithium ion battery comprises: adding phenylalanine dipeptide and N-methylpyrrolidone into a 30L slurry mixing kettle, fully dissolving and dispersing them to obtain a phenylalanine dipeptide solution; adding sodium ferric pyrophosphate, conductive carbon black, polyvinylidene fluoride and phenylalanine dipeptide solution into a 30L slurry mixing kettle according to a mass ratio of pure substances (excluding solvent) of 95.4%:2%:2%:0.6%, stirring evenly, adding N-methylpyrrolidone to adjust the solid content to 51% of the total weight of the slurry, stirring at high speed to disperse evenly, and slowly stirring for 2.5 hours to obtain the positive electrode slurry for a sodium ion battery.
[0058] Example 4
[0059] This embodiment provides a negative electrode slurry for a sodium ion battery, comprising a negative electrode active material hard carbon, a negative electrode conductive agent conductive carbon black, a negative electrode binder carboxymethyl cellulose and styrene-butadiene rubber, a negative electrode solvent pure water and self-assembling peptide nanotubes; the self-assembling peptide nanotubes coat the negative electrode active material and the negative electrode conductive agent;
[0060] The preparation method of the negative electrode slurry of the lithium ion battery comprises: adding carboxymethyl cellulose and pure water into a 30L slurry mixing kettle to disperse to obtain a glue solution. Adding the glue solution, hard carbon, conductive carbon black, and phenylalanine dipeptide into a 30L slurry mixing kettle according to the mass ratio of pure substances (excluding solvent) of 1%:94.4%:2%:0.6%, adding pure water, adjusting the solid content to 53% of the total weight of the slurry, stirring at high speed to disperse evenly, adding styrene-butadiene rubber with a mass ratio of 2%, and continuing to disperse to obtain the negative electrode slurry of the sodium ion battery.
[0061] Example 5
[0062] The present embodiment provides a positive electrode slurry for a lithium ion battery. The preparation method of the positive electrode slurry for a lithium ion battery is to adjust the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, polyvinylidene fluoride and phenylalanine dipeptide solution according to the pure substance (excluding the solvent) from 95.4%:2%:2%:0.6% to 95.95%:2%:2%:0.05%. Except for the above, other conditions are exactly the same as those in Example 1.
[0063] Example 6
[0064] The present embodiment provides a positive electrode slurry for a lithium ion battery. The preparation method of the positive electrode slurry for a lithium ion battery is to adjust the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, polyvinylidene fluoride and phenylalanine dipeptide solution according to the pure substance (excluding the solvent) from 95.4%:2%:2%:0.6% to 94.8%:2%:2%:1.5%. Except for the above, other conditions are exactly the same as those in Example 1.
[0065] Example 7
[0066] The present embodiment provides a positive electrode slurry for a lithium ion battery. The preparation method of the positive electrode slurry for a lithium ion battery is to adjust the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, polyvinylidene fluoride and phenylalanine dipeptide solution according to the pure substance (excluding the solvent) from 95.4%:2%:2%:0.6% to 93.6%:2%:2%:3%. Except for the above, other conditions are exactly the same as those in Example 1.
[0067] Example 8
[0068] The present embodiment provides a negative electrode slurry for a lithium ion battery. The preparation method of the negative electrode slurry for a lithium ion battery adjusts the mass ratio of the glue, graphite, conductive carbon black, and phenylalanine dipeptide according to the pure substance (excluding the solvent) from 1%:94.4%:2%:0.6% to 1%:96.95%:2%:0.05%. Except for the above, other conditions are exactly the same as those in Example 1.
[0069] Example 9
[0070] The present embodiment provides a negative electrode slurry for a lithium ion battery. The preparation method of the negative electrode slurry for a lithium ion battery adjusts the mass ratio of the glue, graphite, conductive carbon black, and phenylalanine dipeptide according to the pure substance (excluding the solvent) from 1%:94.4%:2%:0.6% to 1%:95.8%:2%:1.5%. Except for the above, other conditions are exactly the same as those in Example 1.
[0071] Example 10
[0072] The present embodiment provides a negative electrode slurry for a lithium ion battery. The preparation method of the negative electrode slurry for a lithium ion battery adjusts the mass ratio of the glue, graphite, conductive carbon black, and phenylalanine dipeptide according to the pure substance (excluding the solvent) from 1%:94.4%:2%:0.6% to 1%:94.6%:2%:3%. Except for the above, other conditions are exactly the same as those in Example 1.
[0073] Comparative Example 1
[0074] The present comparative example provides a positive electrode slurry for a lithium-ion battery, which does not contain self-assembling peptide nanotubes, and the preparation method of the positive electrode slurry for a lithium-ion battery does not use phenylalanine dipeptide, that is, the preparation method of the positive electrode slurry for a lithium-ion battery is as follows: lithium nickel cobalt manganese oxide, conductive carbon black, and polyvinylidene fluoride are added into a 30L slurry mixing kettle in a mass ratio of 96%:2%:2% and stirred evenly, N-methylpyrrolidone is added, the solid content is adjusted to 72% of the total weight of the slurry, and the positive electrode slurry for a lithium-ion battery is dispersed evenly by high-speed stirring and defoaming.
[0075] Comparative Example 2
[0076] The present comparative example provides a negative electrode slurry for a lithium ion battery, wherein the negative electrode slurry for the lithium ion battery does not contain self-assembling peptide nanotubes, and the preparation method of the negative electrode slurry for the lithium ion battery does not use phenylalanine dipeptide, that is, the preparation method of the negative electrode slurry for the lithium ion battery comprises: adding carboxymethyl cellulose and pure water into a 30L slurry mixing kettle, and dispersing to obtain a glue solution; adding the glue solution, graphite, and conductive carbon black into a 30L slurry mixing kettle according to a pure substance mass ratio of 1%:95%:2%, adding pure water, adjusting the solid content to 51% of the total weight of the slurry, stirring at a high speed to disperse evenly, adding styrene-butadiene rubber with a mass ratio of 2%, and continuing to disperse to obtain the negative electrode slurry for the lithium ion battery.
[0077] Comparative Example 3
[0078] The present comparative example provides a positive electrode slurry for a sodium ion battery, which does not contain self-assembling peptide nanotubes, and the preparation method of the positive electrode slurry for a sodium ion battery does not use phenylalanine dipeptide, that is, the preparation method of the positive electrode slurry for a sodium ion battery is as follows: sodium ferric pyrophosphate, conductive carbon black, and polyvinylidene fluoride are added into a 30L slurry mixing kettle in a mass ratio of 96%:2%:2% and stirred evenly, N-methylpyrrolidone is added, the solid content is adjusted to 51% of the total weight of the slurry, and the sodium ion battery positive electrode slurry is dispersed evenly by high-speed stirring and defoaming to obtain the positive electrode slurry for a sodium ion battery.
[0079] Comparative Example 4
[0080] The present comparative example provides a negative electrode slurry for a lithium ion battery, which does not contain self-assembling peptide nanotubes, and the preparation method of the negative electrode slurry for a lithium ion battery does not use phenylalanine dipeptide, that is, the preparation method of the negative electrode slurry for a lithium ion battery comprises: adding carboxymethyl cellulose and pure water into a 30L slurry mixing kettle, and dispersing to obtain a glue solution; adding the glue solution, hard carbon, and conductive carbon black into a 30L slurry mixing kettle according to a pure substance mass ratio of 1%:95%:2%, adding pure water, adjusting the solid content to 53% of the total weight of the slurry, stirring at a high speed to disperse evenly, adding styrene-butadiene rubber with a mass ratio of 2%, and continuing to disperse to obtain a negative electrode slurry for a sodium ion battery.
[0081] Control group 1
[0082] This control group provides a lithium-ion battery positive electrode slurry, in which no phenylalanine dipeptide is additionally added in the preparation method of the lithium-ion battery positive electrode slurry. The preparation method of the lithium-ion battery positive electrode slurry is as follows: lithium nickel cobalt manganese oxide coated with peptide nanotubes, conductive carbon black, and polyvinylidene fluoride are added into a 30L slurry mixing kettle in a mass ratio of 96%:2%:2% and stirred evenly, N-methylpyrrolidone is added, the solid content is adjusted to 72% of the total weight of the slurry, and the lithium-ion battery positive electrode slurry is evenly dispersed by high-speed stirring and defoaming. The peptide nanotube-coated lithium nickel cobalt manganese oxide is obtained by the preparation method provided by CN110911655A.
[0083] Application Example 1
[0084] This application example provides an electrode sheet, which uses the electrode slurries of Examples 1-10, Comparative Examples 1-4 and Control Group 1 to be coated on a current collector (the positive electrode slurry is coated on an aluminum foil, and the negative electrode slurry is coated on a copper foil), and then sequentially dried, rolled and die-cut to obtain a lithium ion battery positive electrode sheet, or a lithium ion battery negative electrode sheet, or a sodium ion battery positive electrode sheet or a sodium ion battery negative electrode sheet.
[0085] Application Example 2
[0086] This application example provides a battery, which is obtained by assembling the electrode sheet provided in application example 1, wherein:
[0087] The assembly method of a lithium-ion battery comprises: assembling a lithium-ion battery positive electrode sheet, a lithium-ion battery negative electrode sheet, a ceramic diaphragm, an aluminum-plastic film and a lithium hexafluorophosphate electrolyte to obtain a soft-pack battery, and then chemically dividing the battery into a qualified lithium-ion battery;
[0088] The assembly method of the sodium ion battery comprises: assembling a lithium ion battery positive electrode sheet, a lithium ion battery negative electrode sheet, a ceramic diaphragm, an aluminum-plastic film and a sodium hexafluorophosphate electrolyte to obtain a soft-pack battery, and then chemically dividing the battery into a qualified sodium ion battery.
[0089] The obtained battery information and serial numbers are listed in Table 1.
[0090] Characterization and Testing I: The lithium-ion battery obtained in Application Example 2 was tested for its 10C / 10s pulse performance at room temperature and its cycle performance at 45°C. The results are recorded in Table 1.
[0091] Figure 1 and Figure 2 They are respectively the pulse performance test graphs and the cycle performance test graphs of the lithium ion batteries B, C and D obtained in Application Example 2. Combined with Table 1, it can be seen from the graph that the lithium ion battery composed of the positive electrode plate of the lithium ion battery obtained in Example 1 and the negative electrode plate of the lithium ion battery obtained in Example 2 are superior to the battery composed of the positive electrode plate obtained in Comparative Example 1 and / or the negative electrode plate obtained in Comparative Example 2 in terms of rate performance and high-temperature cycle performance, indicating that whether the electrode slurry scheme of the present invention is implemented in the positive electrode plate and / or the negative electrode plate of the lithium ion battery, the rate performance and / or cycle performance of the battery can be effectively improved.
[0092] Characterization and Test II: The sodium ion battery obtained in Application Example 2 was tested for its 1C discharge curve under room temperature, and the results are recorded in Table 1;
[0093] Figure 31C discharge curve diagram of the sodium battery X and the sodium battery Z obtained in Application Example 2. Combined with Table 1, it can be seen from the figure that the 1C discharge voltage platform of the sodium ion battery composed of the positive electrode sheet of the sodium ion battery obtained in Example 3 and the negative electrode sheet of the sodium ion battery obtained in Example 4 is better than that of the battery composed of the positive electrode sheet obtained in Comparative Example 3 and / or the negative electrode sheet obtained in Comparative Example 4, indicating that whether the electrode slurry scheme of the present invention is implemented in the positive electrode sheet and / or the negative electrode sheet of the sodium ion battery, the polarization of the battery cell can be effectively reduced and the rate performance of the battery can be improved.
[0094] Table 1
[0095]
[0096] Note: “ / ” in Table 1 means not tested.
[0097] It can be seen from Table 1 that:
[0098] When 0% (no addition), 0.05%, 0.6%, 1.5% and 3% self-assembled titanium nanotubes were added to the positive electrode of the lithium-ion battery, the high-rate pulse performance of the battery was significantly improved. The voltage at the end of discharge increased from 3.4091V to 3.4113V, 3.4177V, 3.4268V and 3.4317V, respectively, and the 1C discharge voltage platform of the battery increased from 3.6089V to 3.6102V, 3.6164V, 3.6192V and 3.6224V, respectively. When 0% (no addition), 0.05%, 0.6%, 1.5% and 3% of self-assembled titanium nanotubes are added to the negative electrode of the lithium-ion battery, the high-rate pulse performance of the battery is improved, and the voltage at the end of discharge is increased from 3.4091V to 3.4101V, 3.4153V, 3.4162V and 3.4185V, respectively, and the 1C discharge voltage platform of the battery is increased from 3.6089V to 3.6093V, 3.6123V, 3.6137V and 3.6149V, respectively. When 0.6% of self-assembled titanium nanotubes are added to both the positive and negative electrodes, the termination voltage of the battery's high-rate pulse discharge is increased from 3.4091V to 3.4223V, and the 1C discharge voltage platform is increased from 3.6089V to 3.6178V.
[0099] When no self-assembled titanium nanotubes were added to the positive and negative electrodes, the capacity retention rate of the battery after 1000 cycles of high temperature cycling was 94.6%. When the addition amount in the positive electrode was 0.6% and 3%, the capacity retention rate of the battery after 1000 cycles of high temperature cycling was 95.4% and 94.4%, respectively. When the addition amount in the negative electrode was 0.6% and 3%, the capacity retention rate of the battery after 1000 cycles of high temperature cycling was 95.7% and 93.7%, respectively. When 0.6% of self-assembled titanium nanotubes were added to both the positive and negative electrodes, the capacity retention rate of the battery after 1000 cycles increased from 94.6% to 95.9%. As shown in the above results, when the addition amount of self-assembled titanium nanotubes was 0.6%, the rate performance and high temperature cyclability of the battery were effectively improved; but when the addition amount was 3%, the rate performance of the battery was effectively improved, but it was not conducive to the cycle performance. This is because the addition amount of self-assembled titanium nanotubes is large, which leads to the rate of battery side reactions being accelerated while improving the rate performance of the battery. From the results of group E, it can be seen that the scheme proposed by the present invention and the scheme proposed by CN110911655A can both effectively improve the rate performance of the battery, but in terms of improving the cycle performance, the scheme proposed by the present invention has more advantages. As can be seen from Table 1, the scheme in the present invention can effectively reduce the polarization of the sodium ion battery and improve the rate performance of the sodium ion battery.
[0100] As can be seen from the above, the present invention forms a three-dimensional network in the electrode slurry and in the active layer formed using the electrode slurry by using self-assembling peptide nanotubes to coat the active material and the conductive agent. On the one hand, it can optimize the electron conduction path in the active layer formed using the electrode slurry. On the other hand, the network structure of the peptide nanotubes can further interlock and cooperate with the binder, thereby improving the distribution uniformity of the conductive agent and the binder, enhancing the binding of the active material and the conductive agent and the uniformity of the active layer formed; at the same time, under the influence of the peptide nanotubes distributed in the slurry, during the coating process of the electrode slurry, it is beneficial to limit the floating of the binder and the conductive agent, thereby further improving the uniformity of the electrode sheet in the thickness direction. Therefore, the present invention can achieve effective improvement in the rate performance and cycle performance of the electrode sheet and the resulting battery from the slurry level and the electrode sheet manufacturing side.
[0101] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0103] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. An electrode slurry, characterized in that: The invention comprises an active material, a conductive agent, a binder, a solvent and a self-assembling peptide nanotube; the self-assembling peptide nanotube covers the active material and the conductive agent.
2. The electrode slurry according to claim 1, characterized in that: When the electrode slurry is a positive electrode slurry, the positive electrode slurry includes a positive electrode solvent, and a positive electrode active material, a positive electrode conductor, a positive electrode binder and a first self-assembling peptide nanotube in a mass ratio of x:y:z:m; and x+y+z+m=100%, 85%≤x<100%, 0<y<10%, 0<z<10%, 0<m<5%, 0.5%≤y+z≤10%.
3. The electrode slurry according to claim 2, characterized in that: The positive electrode active material comprises at least one of a lithium ion battery positive electrode active material, a sodium ion battery positive electrode active material, a potassium ion battery positive electrode active material or a magnesium ion battery positive electrode active material; Preferably, the lithium-ion battery positive electrode active material includes at least one of lithium cobalt oxide, ternary materials, lithium-rich manganese-based materials, lithium iron phosphate or lithium iron manganese phosphate; Preferably, the sodium ion battery positive electrode active material, potassium ion battery positive electrode active material or magnesium ion battery positive electrode active material is selected from at least one of layered oxides, polyanion compounds or Prussian blue analogs; Preferably, the positive electrode conductive agent includes at least one of conductive carbon black, carbon nanotubes or graphene; Preferably, the positive electrode binder comprises polyvinylidene fluoride and / or polytetrafluoroethylene; Preferably, the cathode solvent comprises N-methylpyrrolidone; Preferably, the solid content of the positive electrode slurry is 45% to 85%.
4. The electrode slurry according to any one of claims 1 to 3, characterized in that: When the electrode slurry is a negative electrode slurry, the negative electrode slurry includes a negative electrode solvent, and a negative electrode active material, a negative electrode conductor, a negative electrode binder and a second self-assembling peptide nanotube in a mass ratio of a:b:c:n; and a+b+c+n=100%, 85%≤a<100%, 0<b<10%, 0<c<10%, 0<n<5%, 0.5%≤b+c≤10%.
5. The electrode slurry according to claim 4, characterized in that: The negative electrode active main material includes at least one of graphite, hard carbon, silicon-based materials, lithium titanate or metal oxide negative electrode materials; Preferably, the negative electrode conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers or graphene; Preferably, the negative electrode binder comprises at least one of styrene-butadiene rubber, carboxymethyl cellulose or polyacrylic acid; Preferably, the negative electrode solvent includes pure water and / or N-methylpyrrolidone; Preferably, the negative electrode slurry further includes a plasticizer; Preferably, the plasticizer includes at least one of ethylene carbonate, propylene carbonate, 1,3-butanediol or N-methylpyrrolidone; Preferably, the solid content of the negative electrode slurry is 40% to 65%.
6. A method for preparing an electrode slurry according to any one of claims 1 to 5, characterized in that: The preparation method comprises the steps of mixing and dispersing active materials, conductive agents, binders, solvents and self-assembling peptide nanotube raw materials, and stirring and / or standing the raw materials to allow the self-assembling peptide nanotube raw materials to self-assemble, thereby forming the self-assembling peptide nanotubes covering the active materials and the conductive agents to obtain electrode slurry.
7. The method for preparing the electrode slurry according to claim 6, characterized in that: The self-assembling peptide nanotube raw material includes phenylalanine dipeptide; Preferably, the stirring time is 1 to 4 hours.
8. An electrode sheet, characterized in that: The electrode slurry according to any one of claims 1 to 3 is sequentially coated, dried, rolled and divided / die-cut to obtain the electrode slurry.
9. A battery, characterized in that: A composition comprising the electrode sheet according to claim 8.
10. An electrical device, characterized in that: A battery comprising the battery according to claim 9.
Citation Information
Patent Citations
Self-assembled ultrafast charging positive electrode material and lithium ion battery thereof
CN110911655A
Negative plate and battery
CN113113565A